Transborder fugitives, extradition, and political crimes in modern China / Jenny Huangfu Day. - Day, Jenny Huangfu, 1985- (Studies in legal history., 2026)
Uncovering a series of landmark but often overlooked extradition cases between China and foreign powers from the 1860s to the 1920s, this study challenges the prevailing conception that political crimes in China were solely a domestic phenomenon. Extradition and extraterritoriality played an important role in shaping laws and regulations related to political crimes in modern China. China's inability to secure reciprocal extradition treaties was historically rooted in the legacy of extraterritoriality and semi-colonialism. Jenny Huangfu Day illustrates how the fugitive rendition clauses in the Opium War treaties evolved into informal extradition procedures and describes how the practice of fugitive rendition changed from the late Qing to Republican China. Readers will gain an understanding of the interaction between international law, diplomacy, and municipal laws in the jurisdiction of political crimes in modern China, allowing Chinese legal history to be brought into conversation with transnational legal scholarship.